Kinetic analysis of swimming flip-turn push-off techniques - Weimar, W.; Sumner, A.; Romer, B.; Fox, J.; Rehm, J.; Decoux, B.; Patel, J. (Sports, 2019)
The aims of the present study were to examine the influences of different push-off techniques on kinetic and kinematic parameters both in and out of the water. The two techniques were: (1) a push off that was characterized by rapid extension of knees and hips towards the wall, prior to contact (i.e., no countermovement), and, (2) where the swimmer glides into the wall, letting the wall flex the knees in an approximate countermovement or eccentric phase. Twenty trained male and female freestyle swimmers (age 26.1 ± 9.9 years, height 1.61 ± 0.04 m, and weight 65.6 ± 19.3 kg) participated. Data were analyzed by employing two (i.e., land and water) 3 (variables of interest) x 2 (push-off type) repeated measures ANOVAs with the alpha level set a priori at 05. Results indicated that there were significant main effects for peak perpendicular force (p < 0.001), perpendicular impulse (p = 0.018), and velocity at 2.5 m (p = 0.005) on land. However, no significant effects were found between techniques in the water trials. As many of the participants were master swimmers, it is possible that they were unable to approach the wall in the water at the requisite speed to elicit a benefit from the countermovement